Foundations and practice of security : 7th International Symposium, FPS 2014, Montreal, QC, Canada, November 3-5, 2014. Revised selected papers /: 7th International Symposium, FPS 2014, Montreal, QC, Canada, November 3-5, 2014. Revised selected papers. (2015) - Unknown
No abstract available